MULTIPLE PREGNANCIES (Neo Scientific Peer Reviewed Journal, 2024)
Double pregnancies account for 2 to 4% of total births, with a prevalence of 0.9 to 2.4% in Brazil. It is associated with worse maternal and perinatal outcomes. Many conditions, such as severe maternal morbidity (SMM) (potentially life-threatening conditions and maternal near death) and neonatal near death (NNM), have not yet been adequately investigated in the literature. associated with twin pregnancies is probably due to its relatively low prevalence and the need for larger population studies. Thus, the use of the entire population and databases of large, multicenter studies can yield unprecedented results. Because it is a rare condition, it is easier to assess with vital statistics from electronic birth registries. Twin pregnancies have consistently been associated with SMM, maternal failure (MNM), and perinatal morbidity, with even worse outcomes for the second twin, possibly due to some characteristics of delivery, including the safety and availability of appropriate obstetric care for women at high risk of perinatal complications.